N-acetylglutamate synthetase deficiency - literature review - Krystian Wdowiak; Agnieszka Maciocha; Julia Wąż; Aleksandra Witas; Justyna Drogoń; Weronika Chachaj; Natalia Szymkowiak; Ewa Gardocka (Journal of Education, Health and Sport)
Introduction and Objective: N-Acetylglutamate Synthetase Deficiency (NAGSD) is a rare urea cycle disorder, primarily caused by autosomal recessive genetic mutations. Most affected individuals are homozygous for the disease-causing allele. The aim of this publication is to discuss various aspects of N-acetylglutamate synthetase deficiency based on the latest literature. Review Methods: The PubMed database was searched to find scientific articles in which the terms "N-acetylglutamate synthetase," "NAGS deficiency," or "N-acetylglutamate synthetase deficiency" appear in the title, abstract, or keywords. Brief Description of the State of Knowledge:  Symptoms of NAGSD typically appear in the neonatal period. The NAGS enzyme is essential for catalyzing the synthesis of N-acetylglutamate, an allosteric activator of carbamoylphosphate synthetase 1 (CPS1), crucial for the urea cycle. Key biochemical markers include elevated ammonia, glutamine, and alanine; decreased citrulline; and respiratory alkalosis. Hyperammonemia is the main clinical feature, manifesting as nausea, vomiting, cognitive impairment, seizures, and, in severe cases, coma or death. Genetic testing remains the cornerstone of diagnosis, enabling identification of specific mutations. Treatment involves carbamylglutamate, an NAG analog that activates CPS1. Summary:  Expanding research aims to explore novel treatments in NAGSD, dietary strategies, and the safety of current therapies during pregnancy.